Linguistic diversity, official language choice and human capital - Laitin, David D.; Ramachandran, Rajesh (Journal of development economics, 2022)
The mechanisms linking high ethnic fractionalization (ELF) to poor economic outcomes in sub-Saharan Africa remain obscure. This paper proposes that high ELF raises the costs of implementing indigenous language education policies, and that the concomitant reliance on colonial languages as media of instruction lowers human capital development, our measure for economic failure. Exploiting the fact that 101 linguistic groups in sub-Saharan Africa cross country borders that have different language-use-in-education systems, we are able to include ethnicity fixed effects in our regression estimates. This allows us to control for a large set of cultural, geographical, and environmental factors that could confound the estimates. Our within-ethnicity estimates show that even the partial use of indigenous languages in schools is associated with an economically meaningful increase in the probability of reading for individuals with seven or fewer years of schooling. Once including language-use-in education as a regressor, the coefficient for ELF in explaining lower human capital turns insignificant. Our results suggest that retention of colonial languages is an important factor in explaining economic failures in postcolonial Africa.